Isu-Isu Gender dalam Bimbingan dan Konseling Multibudaya: Pentingnya Peran Gender dan Cara Sosialisasi Gender Melalui Budaya (Studi Literatur) - Riza Melinda; Bakhrudin All Habsy (Jurnal Sosial Teknologi, 2026)
Gender issues in multicultural counseling are becoming increasingly important because the complexity of gender identity and differences in cultural values ​​can trigger psychological stress, thus requiring counselors to be sensitive, inclusive, and able to create a safe space for clients.This research aims to examine gender issues in multicultural counseling and their implications for encouraging the development of more inclusive and effective counseling services for diverse clients. This research was compiled using a literature review approach, examining various theories, methods, and previous research findings related to gender issues in multicultural counseling. This review revealed several gaps in the research that remain largely unexplored. At the same time, this approach also helps to develop a more comprehensive understanding of how cultural diversity influences counseling practice. Interestingly, emerging findings suggest that a deep understanding of the relationship between culture and gender roles is no longer merely an add-on, but a primary need. Without it, counseling services risk bias and a lack of responsiveness. Therefore, multicultural counselors are required to have strong cultural awareness to see clients more holistically without becoming trapped by assumptions or stereotypes. Ultimately, when the approach used truly takes this complexity into account, multicultural counseling can be a space that not only helps individuals navigate gender issues, but also supports their psychological well-being more holistically amidst diverse social realities